FRI0002 Il-1 receptor antagonist (il-1ra) treatment is associated with improvement of anaemia in rheumatoid arthritis. (1st June 2001) - Kay, J; Bryant, S; Cravets, MW; McCabe, D
Abstract : Background: Anaemia occurs frequently as an extraarticular complication of rheumatoid arthritis (RA) and usually correlates with markers of disease activity. Interleukin (IL)-1, levels of which are elevated in serum and synovial tissue of patients with RA, inhibits erythropoiesis in vitro . Serum IL-1 levels are higher in anaemic patients with RA than in those without anaemia. 1 Objectives: To determine if IL-1 receptor antagonist (IL-1ra) is associated with improvement of anaemia in patients with rheumatoid arthritis. Methods: We observed the effect of daily IL-1ra treatment in anaemic patients with active, severe RA who were enrolled in a 24-week, double-blind, randomised, placebo-controlled multicenter study of IL-1ra therapy. Fifty (14.2%) of the IL-1ra-treated patients and 13 (10.7%) of the placebo-treated patients were anaemic, defined as HCT < = 34%, 2 upon initiation of drug therapy. Results: Improvement in anaemia was stratified according to the increase after 24 weeks of treatment. Although the number of anaemic patients enrolled in this trial was small, more patients treated with IL-1ra exhibited improvement in HCT after 24 weeks of drug than did patients receiving placebo: Conclusion: Anaemia improved in patients taking each of the 3 doses of IL-1ra. Interestingly, 3 of the 7 IL-1ra-treated patients with > = 6 vol-% improvement in their HCT did not meet ACR20 response criteria. Thus, IL-1ra therapy may improve anaemia in RA patients independently of its effect on articular disease activity. Further study of IL-1ra therapy in anaemic patients with RA is warranted to clarify its effects on erythropoiesis and the impact of these changes in Hct on clinical status. References: Maury, et al . Ann Rheum Dis. 1988;47:972 Pincus, et al . Am J Med. 1990;89:161